Argumentação no ensino de proporção em livros didáticos - Fraga, Fabio Fontes (2022)
This study aimed to identify the argumentation categories used by eleven mathematics textbooks, of the 7th grade, of basic education, adopted by the guide of the National Textbook Plan, the PNLD, of 2020, in relation to the proportion content. Based on several authors, such as Toulmin (2006), Balacheff (1988), Sales (2010), Attie (2016), Duval (1993), Caldato et al (2017), Nasser and Tinoco (2003), Sasseron and Carvalho (2011), among others, we defined the concepts of argumentation, explanation, justification, proof and demonstration, which are important for our work. Regarding the methodology, we consider that our research can be characterized as qualitative, with exploratory, documentary and descriptive aspects. For the development of our research, we start from the central question: What type or categories of argumentation are addressed in mathematics textbooks recommended by the PNLD guide, in relation to proportion teaching? From this question, we designed as objective to identify the categories of argumentation used by the textbooks recommended by the guide of the National Plan of Textbook - PNLD (BRASIL, 2020), in relation to the teaching of proportions. Regarding data collection, we made a brief historical approach on the subject, as well as a mapping of research related to the teaching of proportion and we carried out a search in the textbooks mentioned, in order to identify the categories of argument used in the teaching of proportion. Finally, after the analysis, we present as the main result the predominance of explicative arguments in the books considered.